Nocturnal Asthma: Proof-of-Concept Open-Label Study with Delayed-Release Prednisone. Issue 1 (December 2015) - Alavoine, Loubna; Taillé, Camile; Ball, Julie; Knauer, Christine; Witte, Stephan; Kent, Jeffrey; Aubier, Michel
Abstract Introduction Many inflammatory conditions, such as asthma, show circadian symptoms that are worse at night. Delayed-release prednisone was developed for bedtime administration to optimize inhibition of nocturnally elevated pro-inflammatory cytokines. A proof-of-concept study was undertaken to examine the impact of delayed-release prednisone on nocturnal awakenings in patients with asthma requiring treatment with oral steroids. Methods In this single-center, open-label study, patients receiving long-term treatment with conventional prednisone administered at 08:00 h were switched to 4 weeks of treatment with the same dose of delayed-release prednisone given at 22:00 h. The primary efficacy endpoint was the change in number of nocturnal awakenings during the final 2 weeks of each treatment phase. Results Seven patients received treatment with delayed-release prednisone. Mean nocturnal awakenings because of asthma decreased from 10.0 ± 5.45 with conventional prednisone to 2.1 ± 4.41 with delayed-release prednisone, a mean reduction of −7.9 ± 6.07 (82.7% reduction). Delayed-release prednisone was generally well tolerated, and there were no unexpected safety findings. Conclusions Although the size of the efficacy population was too small to detect any statistically significant changes in nocturnal asthma control, this proof-of-concept study suggests that nighttime administration of delayed-release prednisone provides better asthma symptom control compared with morning administration of conventional prednisone. Funding Horizon Pharma, Inc (formerly Nitec Pharma GmbH).